MIGA Annual Report 2015 - Multilateral Investment Guarantee Agency (Washington, DC: World Bank Group, 2015)
In fiscal year 2015, the Multilateral Investment Guarantee Agency (MIGA) issued a total of $2.8 billion in guarantees for 40 projects in MIGA's developing member countries. An additional $3.2 million was issued under MIGA-administered trust funds. Projects spanned regions and sectors, with 60 percent of this new issuance falling into at least one of MIGA's priority areas. At the end of the year, MIGA's gross exposure was $12.5 billion. Of this, $4.8 billion was ceded to MIGA's reinsurance partners. MIGA’s mission is to support economic growth, reduce poverty, and improve people’s lives. In order to achieve this, the agency needs a clear understanding of the development outcomes of the projects it supports. MIGA’s Development Effectiveness Indicator System (DEIS) collects a common set of indicators from clients to demonstrate results across all projects: volume of investment catalyzed, direct employment, taxes paid, and value of locally procured goods. It also measures sector-specific indicators. MIGA's $2.8 billion issuance in fiscal year 2015 is expected to catalyze an additional $9.8 billion in public and private co-investment.